Analisis Eksegetis Makna Allon Paraklēton dalam Injil Yohanes: Signifikansi Kehadiran Roh Kudus sebagai Pengganti Personal Kristus - Rosalia Enny Astuti; Laurentius Prasetyo (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2026)
This study aims to systematically reconstruct the doctrine of the Holy Spirit (Pneumatology) in the Gospel of John, specifically through an analysis of the term Allon Paraklēton, and to evaluate its relevance for spiritual life in the contemporary era. As a qualitative study, this research employs a literature review design, utilizing theological hermeneutics and exegetical analysis of primary Biblical texts and systematic theology literature. The findings, established through source triangulation, emphasize that the term allon specifically refers to "another of the same kind," positioning the Holy Spirit as Christ’s personal replacement who is equal in divinity. Systematically, the personality of the Holy Spirit is validated through the possession of intellect, emotion, and will, playing a vital role in the regeneration and sanctification of believers. In the ecclesiological dimension, the Holy Spirit is understood as the principle of communion (communio) that unites the Church as the Mystical Body of Christ. The practical significance of this doctrine is found in the Holy Spirit’s role as a "decoder" of truth amidst the challenges of the post-truth era characterized by mass disinformation. In conclusion, the Holy Spirit serves as the dynamic bridge of salvation history, restoring the spiritual vitality of the congregation and ensuring the continuity of Christ's mission in the world.AbstrakPenelitian ini bertujuan untuk merekonstruksi secara sistematis doktrin Roh Kudus (Pneumatologi) dalam Injil Yohanes, khususnya melalui analisis terhadap istilah Allon Paraklēton, serta menganalisis relevansinya bagi kehidupan spiritual umat di era kontemporer. Sebagai studi kualitatif, penelitian ini menerapkan desain studi literatur dengan pendekatan hermeneutika teologis dan analisis eksegetis terhadap teks primer Alkitab serta literatur teologi sistematika. Temuan penelitian melalui teknik triangulasi sumber menegaskan bahwa penggunaan istilah allon secara spesifik merujuk pada "Pribadi lain dari jenis yang sama," yang memposisikan Roh Kudus sebagai pengganti personal Kristus yang setara dalam keilahian. Secara sistematika, kepribadian Roh Kudus divalidasi melalui kepemilikan atribut intelek, emosi, dan kehendak yang berperan vital dalam karya regenerasi dan pengudusan jemaat. Dalam dimensi eklesiologis, Roh Kudus dipahami sebagai prinsip persekutuan (communio) yang menyatukan Gereja sebagai Tubuh Mistik Kristus. Signifikansi praktis dari doktrin ini ditemukan pada peran Roh Kudus sebagai "pemecah sandi" (decoder) kebenaran di tengah tantangan era pasca-kebenaran (post-truth) yang penuh disinformasi. Kesimpulannya, Roh Kudus adalah jembatan dinamis sejarah keselamatan yang memulihkan vitalitas spiritual jemaat dan menjamin keberlangsungan misi Kristus di dunia.